OCP : - Stuns, Doug (Sybex, 2002)
Here's the book you need to prepare for Exam 1Z0-032: Oracle9i Database: Fundamentals II. In-depth coverage of official exam objectives. Practical information on implementing and managing Oracle9i databases. Hundreds of challenging review questions, in the book and on the CD